Formation of polymeric microcapsules with encapsulated hexane by extraction-coacervation technique - Borova, Solomiya; Serdiuk, Vitalii; Shevchuk, Oleh (Видавництво Львівської політехніки, 2013)
The formation of polymer microcapsules containing encapsulated hexane on the basis of synthesized heterofunctional tetrapolymer as shell-building material using the developed “extraction-coacervation” method of microencapsulation was performed. The effect of process parameters on the final size of microcapsules and efficiency of hexane encapsulation was studied.
Keywords: heterofunctional tetrapolymer; microcapsules; microencapsulation